Analisis Pengaruh Inflasi, Produk Domestik Bruto (PDB), Dan Nilai Tukar Terhadap Tabungan Mudharabah Pada Bank Umum Syariah (Periode 2013-2017) - Rita Nur Wahyuningrum; Aan Zainul Anwar (JESI (Jurnal Ekonomi Syariah Indonesia), 2018)
This study aims to analyze the effect of inflation, gross domestic product (GDP) and rupiah exchange rate on Mudharabah savings in Islamic banking in Indonesia. The data used is time series data for the period March 2013 to September 2017, which was published by Bank Indonesia from the Islamic Banking Statistics Report and the Central Statistics Agency. The technique of analyzing the research is qualitative with the method of Multiple Linear Regression. The results of this study indicate that simultaneously the Inflation, Gross Domestic Product (GDP) and Exchange Rate variables together have a significant effect on Mudharabah Savings. While partially only the Exchange Rate variable has a significant effect on Mudharabah Savings. Inflation Variables and Gross Domestic Product (GDP) have no significant effect on Mudharabah Savings. Keyword: inflation, gross domestic product, exchange rate, mudharabah saving